Two-Dimensional Finite Element Analysis of Piled Raft Coefficient Settlement Ratio on Clays - Christian William Munaba; Aswin Lim; Arif Yunando Soen (Indonesian Geotechnical Journal, 2022)
Nowadays, designing a piled raft foundation is challenging because the behavior is three-dimensional. For some engineers, a three-dimensional analysis might not be affordable due to more costly than a two-dimensional analysis. In this study, 2D Finite element analysis – axisymmetric was used to study the piled raft foundation. The pile diameter and pile length were varied to investigate the relation between piled raft coefficient and load-settlement. In addition, the load transfer mechanism between the raft part and the pile part in clayey soils is also examined. The results show the longer the pile and the larger the diameter, the greater the load carried by the pile and the smaller the settlement. Increase in pile length by 5 m, resulting in a load transfer of 2% to 6% from a raft to pile, and reduced settlement by 2% to 3%. Furthermore, A 0.5 m increase in pile diameter results in an 8% to 25% load transfer from a raft to pile, and a 2% to 7% reduction in a settlement. The soil consistency affects the load distribution and settlement of the pile-raft foundation system. The higher the soil consistency, the smaller the amount transferred to the pile, and the higher the effectiveness of the pile in reducing the settlement that occurs.